(untitled) (Chemical Engineering Research Bulletin, 2026)
In this study, Oryza sativa straw (RS), Eucalyptus globulus sawdust (SD), and Cocos nucifera (CC) coir were chemically modified with sulfuric acid to develop a biodegradable cationic adsorbent. The Feasibility of the modified cellulosic materials as adsorbent for the removal of reactive dye and improvement of water quality parameters was investigated. FTIR analysis was conducted to find out the changes that occurred in the surface of the materials for the modifications and the treated effluent was assessed with UV-VIS spectroscopy to detect the changes in color concentration and water quality indicators (BOD, COD, TDS, TSS, pH, etc.). FTIR analysis of the surface of the treated material showed the existence of different functional groups (C-H, O-H, and C=C) which enhanced, disappeared or shifted after modification with sulfuric acid and treatment. According to the study’s findings, modified CC led to 75.86% elimination of dye from the wastewater, making it the most efficient method for decolorizing effluent. A 1.0 gm adsorbent dosage of modified RS used at room temperature resulted in the largest BOD reduction, which was 67.5%. With 1 gm of adsorbent dosage, modified SD showed the greatest COD reduction, which was 62.125%. And after utilizing modified RS, TDS showed the least reduction (just about 17.3% reduction). Modified CC was responsible for the highest amount of TSS and pH reduction with a 1.0 gm dose (38.24% and 22.85%). This study indicated that a higher dosage of adsorbents resulted in more adsorption capacity of water contaminants, which can be attributed to the fact that a greater surface area was available for adsorption. However, after a certain period of time, adsorbents exhibited a decline in adsorption of water contaminants. Chemical Engineering Research Bulletin: 24 (Issue 1): 105-112